Partial Discharge Characteristics of C3F7CN Gas Mixture Using the UHF Method - Loizos Loizou; Qinghua Han; Lujia Chen; Qiang Liu; Mark Waldron; Gordon Wilson; Roberto Fernandez Bautista; Malcolm Seltzer-Grant (Energies, 2022)
Manufacturing or assembly defects in gas-insulated equipment can introduce field enhancements that could lead to partial discharge (PD). This paper examines the PD characteristics of SF6 alternatives considered for potential application to retro-filling existing SF6-designed equipment. The PD performance of the C3F7CN/CO2 gas mixture and SF6 were characterised adopting the ultra-high frequency (UHF) method and investigated for different defect configurations, pressures, and gas mediums. Hemispherical rod-plane and plane-to-plane configurations with needle on the high-voltage (HV) and ground electrodes were used to mimic conductor and enclosure protrusion defects, respectively. The results demonstrate that with a needle length of 15 mm, the 20% C3F7CN/80% CO2 gas mixture had almost half the partial discharge inception and extinction voltages (PDIV/EV) of SF6. For less divergent fields, the 20% C3F7CN/80% CO2 gas mixture demonstrated a comparable PDIV/EV performance as SF6. The phase-resolved PD patterns of the 20% C3F7CN/80% CO2 gas mixture demonstrated a 3-stage transition phase that was not observed with SF6, which could be due to the discharge mechanism of the weakly attaching CO2 gas used within the mixture.